Efforts to Extend the Human Lifespan: Separating Fact from Fiction - Driver, Jane A. (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
After retirement, older people often find themselves far from their children and grandchildren, and many spend their last years isolated and alone. As traditional concepts of family and social institutions fragment, social networks weaken, leading to an epidemic of loneliness, and substance abuse and suicide in developed countries. In fact, life expectancy in the US has dropped for the past few years, in large part due to a dramatic increase in suicide and drug overdose (ref). None of these social problems is likely to be solved by metformin. They point to a crisis of identity and meaning, an existential crisis. In this context, one might wonder if we are already seeing the effects of tinkering with our lifespan. There are many more conclusions one could draw about the implications of longevity, many of which have been elegantly described in Beyond Therapy: Biotechnology and the Pursuit of Happiness, published by the President’s Council on Bioethics, which I used as a reference for this talk. I hope I have been successful in providing a 10,000-foot view of the questions of efforts to extend human longevity and its implications that will provoke thought and discussion. I would like to end these reflections by turning back to my favorite transhumans. The reason we love superheroes is not for their superior strength or intelligence, but their characters. They use their powers to protect and serve humanity rather than dominate or annihilate it. It is not their gadgetry that makes them great, but how they use it to save the vulnerable. Even as a small child I knew that if everyone acted the way they did, the world would be a better place. The moral of every story was that the “enhancement” humanity needed would not come as the fruit of technology, but of virtue.
Keywords: loneliness; substance abuse; suicide; drugs; identity; meaning; longevity; lifespan; the true transhuman; betterment of the world; virtue